Analysis of the Impact of the Independent Curriculum Implementation on the Moral Development of Students at YASPIM Taruna Private Vocational High School Sei Glugur - Sebayang, Jerry Vlandika (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the impact of the Independent Curriculum implementation on the moral development of students at YASPIM Taruna Private Vocational High School Sei Glugur. The Independent Curriculum, as an educational innovation focusing on learning freedom and character development, is expected to produce students who are not only academically competent but also morally upright. This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings reveal that the implementation of the Independent Curriculum has a positive influence on students’ moral improvement, particularly in aspects of responsibility, discipline, and mutual respect. However, challenges remain, such as limited teacher understanding of the curriculum’s concept and time constraints in project-based learning activities. Therefore, continuous training and mentoring for teachers are necessary to optimize the implementation of the Independent Curriculum in shaping students’ moral character.